Translation reprogramming by eIF3 linked to glioblastoma resistance. (17th September 2020) - Bertorello, Juliette; Sesen, Julie; Gilhodes, Julia; Evrard, Solène; Courtade-Saïdi, Monique; Augustus, Meera; Uro-Coste, Emmanuelle; Toulas, Christine; Moyal, Elizabeth Cohen-Jonathan; Seva, Catherine; Dassi, Erik; Cammas, Anne; et al.
Abstract: Intrinsic resistance to current therapies, leading to dismal clinical outcomes, is a hallmark of glioblastoma multiforme (GBM), the most common and aggressive brain tumor. Understanding the underlying mechanisms of such malignancy is, therefore, an urgent medical need. Deregulation of the protein translation machinery has been shown to contribute to cancer initiation and progression, in part by driving selective translational control of specific mRNA transcripts involved in distinct cancer cell behaviors. Here, we focus on eIF3, a multimeric complex with a known role in the initiation of translation and that is frequently deregulated in cancer. Our results show that the deregulated expression of eIF3e, the e subunit of eIF3, in specific GBM regions could impinge on selective protein synthesis impacting the GBM outcome. In particular, eIF3e restricts the expression of proteins involved in the response to cellular stress and increases the expression of key functional regulators of cell stemness. Such a translation program can therefore serve as a double-edged sword promoting GBM tumor growth and resistance to radiation.